NSs amyloid formation is associated with the virulence of Rift Valley fever virus in mice - Léger, Psylvia; Nachman, Eliana; Richter, Karsten; Tamietti, Carole; Koch, Jana; Burk, Robin; Kummer, Susann; Xin, Qilin; Stanifer, Megan; Bouloy, Michèle; Boulant, Steeve; Kräusslich, Hans-Georg; et al. (Nature Communications, 2020)
Amyloid fibrils result from the aggregation of host cell-encoded proteins, many giving rise to specific human illnesses such as Alzheimer's disease. Here we show that the major virulence factor of Rift Valley fever virus, the protein NSs, forms filamentous structures in the brain of mice and affects mortality. NSs assembles into nuclear and cytosolic disulfide bond-dependent fibrillary aggregates in infected cells. NSs structural arrangements exhibit characteristics typical for amyloids, such as an ultrastructure of 12 nm-width fibrils, a strong detergent resistance, and interactions with the amyloid-binding dye Thioflavin-S. The assembly dynamics of viral amyloid-like fibrils can be visualized in real-time. They form spontaneously and grow in an amyloid fashion within 5hours. Together, our results demonstrate that viruses can encode amyloid-like fibril-forming proteins and have strong implications for future research on amyloid aggregation and toxicity in general. Rift Valley fever virus (RVFV) can cause severe diseases in humans, including encephalitis. Here the authors show that NSs, the major virulence factor of RVFV, is an amyloidogenic protein forming fibrils in infected mouse brains and causing increased mortality in mice.